Structural Intimacies : Sexual Stories in the Black AIDS Epidemic - Mackenzie, Sonja, 1973- (Book collections on Project MUSE., 2013)
This book brings together scholarship on the structural dimensions of the AIDS epidemic and the social construction of sexuality to address the continuing HIV epidemic in the Black population. It asserts that shifting forms of sexual stories - structural intimacies - are emerging and presents a compelling argument: in an era of deepening medicalization of HIV/AIDS, public health must move beyond individual-level interventions to community-level health equity frames and policy changes.